ANALISIS STRUKTUR PASAR INDUSTRI RUMAH TANGGA SASIRANGAN DI KOMPLEK MANARAP KABUPATEN BANJAR - MUHAMMAD RIFQI SYAHRIJAL; NAI'MATUL AUFA (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2019)
This study focused on market structure analysis of home industry Sasirangan in Menarap, KertakHanyar, Banjarto determine market structure type. The purpose of the study to determine marketstructure and determine conditions of competition in sasirangan home industry. The method usedis quantitative descriptive, which is research that is shown to describe the existing phenomena byusing individual or group characteristic numbers. Technique are collecting questionnaire anddocumentation data. Data analysis techniques by knowing market share, market concentration ofCR4 to know market structure. The results showed that the highest market share is Hai***Craftsmen at 11.31%, and CR4 concentration ratio indicate that structure market Sasirangan inMenarap is Monopolistic Competetion with percentage ratio of 32.58%. The results of the studyshowed that the structure market is a Monopolistic Competetion with similar products but thereis competition due to a slight differentiation in terms of quality and marketing.Keywords : 1; Market Structure 2; Condition 3; Marketing 4; Produk